Association between bacterial strain type and host biomarkers in Clostridium perfringens infected goats. (November 2017) - Khan, Mumtaz Ali; Durrani, Aneela Zameer; Khan, Sher Bahadar; Khan, Muhammad Arif; Sheikh, Ali Ahmad; Khan, Naimat Ullah; Prince, Kashif; Ullah, Naimat; Khan, Azmat Ullah
Abstract: The study project was designed to determine the effects of Clostridium perfringens type D infection on hematological and biochemical parameters in goats. Purposive blood samples were collected from 6 healthy and 12 diseased goats positive for C. perfringens infection. Neither the animals nor their mother were vaccinated against Clostridium perfringens from whom samples were obtained. Study was carried out in two different topographic areas; hilly (district Swat) and plain (district Mardan) of Khyber Pakhtunkhwa, Pakistan but nonsignificant (P > 0.05) statistical difference was recorded between the prevalence of Clostridium perfringens infected goats. Mean erythrocytes count (RBC) and hemoglobin level decreased significantly (P < 0.05) while the white blood cells (WBC) increased significantly (P < 0.05) in diseased animals compared to the healthy animals. However non-significant differences (P > 0.05) were observed in packet cell volume (PCV) and platelets count in healthy and diseased animals. According to biochemical analysis, a significant increase (P < 0.05) in liver enzymes, total bilirubin, serum creatinine, blood urea and glucose was recorded in diseased goats. . The results demonstrated that fluctuation in most of the mean hematological values remained within the normal range however the mean liver enzymes, total bilirubin, serum creatinine, blood urea and glucose levels gone beyond the normal levels which demonstrated severe damages to liver and kidneys. Highlights: The prevalence of type A Clostridium perfringens is more than type B and D. The infection is more in farm animals than the household and pastoral. Prevalence is more in high and colostrums fed animals. Fattay and lean animals are more prone to infection than moderate.